Composition of Stand and Growth Dynamics of Black Cardamom (Amomum subulatum) in Different Agroforestry Habitats in Bhutan - Bhakti Sharma Koirala; Bhagat Suberi; Rekha Chhetri; Thubten Gyeltshen (Pandawa Institute, 2023)
The composition and arrangement of tree species at different altitudes play a vital environmental role in the growth of Black Cardamom (Amomum subulatum) in Bhutan. The present study assesses agroforestry tree species composition and factors affecting the growth of A. subulatum in different habitat types. Altitudes were sorted into three different altitudinal bands (low, mid, and high) and each altitudinal band in three different habitats (timber tree, fodder tree, and mixed tree habitat) was assessed. The sampling of 48 plots was made for each habitat and the plot size was 20×20 m. In total, 144 plots were sampled systematically within the selected altitudinal bands in three different habitats. The 56 ecologically important agroforestry shade tree species were used for growing A. subulatum. Tree species preference of A. subulatumchanged based on different altitudes and habitat types [F(2, 33) = 45.672, P = .001]. Critical factors affecting the growth are tree canopy cover (r = –0.461) and infested A. subulatum stems (r = –0.765). The increasing number of infested stems retarded the growth and dense canopy cover or open canopy reduces the growth rate of A. subulatum. Overall, growth was suitable in timber tree habitat at mid altitudes, where Alnus nepalensis was the dominating species having 41.40% canopy cover with low pest and disease-infested A. subulatum stems. Significantly, the lower altitudinal band and the fodder tree habitats were found to be unsuitable for growth (p < 0.05). Thus, appropriate site selection, canopy cover and altitude could provide optimum growth.